Peoples involvement in rural development
Panchayati Raj Reform has beenn rucurring subject for debate since the early 1960s. Various states have constituted Commissions/Committees from time to time to probe into the functioning of the Panchayati Raj Institutions(PRIs), to identify the structural dificiencies and functional maladies in the PRIs and to suggest suitable remedial measure. For example, in Maharashtra, Nasik Committee of 1961, in Karnataka, Basappa Committee of 1963, in Andhra Pradesh, Narashimhan Committee of 1972 and in Rajasthan, G.L. Vyas Committee of 1973. It has been noticed that there is a wide gap, generally between seriousness in constituting a committee/commission on PRIs and seriousness in accepting and implementing recommandatio
Keywords: Women; Village Panchayats; Rural Women; Rural Development; Panchayati Raj; Karnataka; Rural Development - Citizen Participation